An Analysis of Localization Problems and Solutions in Wireless Sensor Networks - Brito,Lina M. Pestana Leão de (2008)
Determining the localization of nodes in a Wireless Sensor Network is a very important task, which involves collaboration between sensor nodes. Localization is a fundamental service since it is relevant to many applications and to the network main functions, such as: routing, communication, cluster creation, network coverage, etc. Collaboration is essential to self-localization, so that localization can be accomplished by the nodes themselves, without any human intervention. In this paper, we first analyze the key aspects that have to be considered when designing or choosing a solution for the localization problem. Then, we present the types of current localization algorithms, making a broad comparison among the most relevant algorithms. With this comparative analysis, we aim at identifying a localization algorithm suitable to the specific problem of forests environmental monitoring, to be applied in the context of the Foresmac European project.